Hydrogel platform facilitating astrocytic differentiation through cell mechanosensing and YAP-mediated transcription - Zhongqian Liu; Shijie Mao; Yubin Hu; Feng Liu; Xiaowei Shao (Materials Today Bio, 2023)
Astrocytes are multifunctional glial cells that are essential for brain functioning. Most existing methods to induce astrocytes from stem cells are inefficient, requiring couples of weeks. Here, we designed an alginate hydrogel-based method to realize high-efficiency astrocytic differentiation from human neural stem cells. Comparing to the conventional tissue culture materials, the hydrogel drastically promoted astrocytic differentiation within three days. We investigated the regulatory mechanism underlying the enhanced differentiation, and found that the stretch-activated ion channels and Yes-associated protein (YAP), a mechanosensitive transcription coactivator, were both indispensable. In particular, the Piezo1 Ca2+ channel, but not transient receptor potential vanilloid 4 (TRPV4) channel, was necessary for promoting the astrocytic differentiation. The stretch-activated channels regulated the nuclear localization of YAP, and inhibition of the channels down-regulated the expression of YAP as well as its target genes. When blocking the YAP/TEAD-mediated transcription, astrocytic differentiation on the hydrogel significantly declined. Interestingly, cells on the hydrogel showed a remarkable filamentous actin assembly together with YAP nuclear translocation during the differentiation, while a progressive gel rupture at the cell-hydrogel interface along with a change in the gel elasticity was detected. These findings suggest that spontaneous decrosslinking of the hydrogel alters its mechanical properties, delivering mechanical stimuli to the cells. These mechanical signals activate the Piezo1 Ca2+ channel, facilitate YAP nuclear transcription via actomyosin cytoskeleton, and eventually provoke the astrocytic differentiation. While offering an efficient approach to obtain astrocytes, our work provides novel insights into the mechanism of astrocytic development through mechanical regulation.